Story of the life satisfaction of a group of retired domestic workers in South Africa: A qualitative study - Cronje, E. M (Social Work/Maatskaplike Werk, 2002)
In this article the story of the life satisfaction of a group of elderly Black South African retired women "ho had worked as domestic workers is told in different voices. On the basis of previous research I had expected that Black women in a low-status occupation would not have a significant measure of life satisfaction, but I was surprised by their degree of life satisfaction, their sense of meaningfulness, their feelings of achievement, and their pride in themselves and their children. For most of these women their church activities are very important and enjoyable, and the wellbeing of their children and grandchildren is also very important to them - many are involved with the care of their grandchildren. Most of them live with their children and/or other relatives, and feel, in their contributions to the household and the care of the grandchildren, that they are still useful. In spite of the "triple jeopardy" (age, poverty and ethnicity) that confronts elderly Black people , these women display a strong resilience. The following words describe in essence the feelings of most of them about life and themselves: "My life is very meaningful; I have achieved a lot" - could ageing be more successful than this?